ANALISIS TINGKAT KESEHATAN KOPERASI: (Studi Kasus Pada Koperasi Kredit Asisi Tahun 2011 – 2015) - Turmono Turmono (Jurnal Co Management, 2019)
The cooperatives, in accordance with its identity will all the time prioritize the service for and welfare of its members properly. The research is intended to know the soundness rate of Asisi Credit Cooperatives year 2011 - 2015 based on Regulation of State Minister for Cooperatives and Small and Medium Scale Business of The Republic of Indonesia Number: 20/Per/M.KUKM/XI/2008 regarding guidance of valuation of Soundness of Saving and Loan Cooperatives (KSP) and Cooperatives Saving and Loan Unit (USP Koperasi) relating to the aspects of Equity, Productive Assets Quality, Management, Liquidity, Efficiency, Independence and Growth as well as Cooperatives Identity. This research is the descriptive evaluation research type. The research subject is the Asisi Credit Cooperatives. The data analysis technique in this research applies the descriptive analysis. In this research the data is gathered through documentation and interview methods. The result of this research indicates that the soundness rate of Asisi Credit Cooperatives year 2011 - 2015 is in quite sound category with average score 69,64.